Hepatocellular carcinoma induces body mass loss in parallel with osmolyte and water retention in rats - Kidoguchi, Satoshi; Kitada, Kento; Nakajima, Kazuki; Nakano, Daisuke; Ohsaki, Hiroyuki; Kittikulsuth, Wararat; Kobara, Hideki; Masaki, Tsutomu; Yokoo, Takashi; Takahashi, Kazuo; Titze, Jens; Nishiyama, Akira (Life Sciences, 2022)
Aims: The number of cancer survivors with cardiovascular disease is increasing. However, the effect of cancer on body fluid regulation remains to be clarified. In this study, we evaluated body osmolyte and water imbalance in rats with hepatocellular carcinoma. Main methods: Wistar rats were administered diethylnitrosamine, a carcinogenic drug, to establish liver cancer. We analyzed tissue osmolyte and water content, and their associations with aldosterone secretion. Key findings: Hepatocellular carcinoma rats had significantly reduced body mass and the amount of total body sodium, potassium, and water. However, these rats had significantly increased relative tissue sodium, potassium, and water content per tissue dry weight. Furthermore, these changes in sodium and water balance in hepatocellular carcinoma rats were significantly associated with increased 24-h urinary aldosterone excretion. Supplementation with 0.25% salt in drinking water improved body weight reduction associated with sodium and water retention in hepatocellular carcinoma rats, which was suppressed by treatment with spironolactone, a mineralocorticoid receptor antagonist. Additionally, the urea-driven water conservation system was activated in hepatocellular carcinoma rats. Significance: These findings suggest that hepatocellular carcinoma induces body mass loss in parallel with activation of the water conservation system including aldosterone secretion and urea accumulation to retain osmolyte and water. The osmolyte and water retention at the tissue level may be a causative factor for ascites and edema formation in liver failure rats.
CRIS-Team Scopus Importer:2021-12-17
Keywords: Body fluid; Catabolism; Glucocorticoid receptor; Hepatocellular carcinoma; Mineralocorticoid receptor; Water conservation